Prealgebra - Marecek, Lynn; Anthony-Smith, MaryAnne; Open Textbook Library (Open Textbook Library, 2015)
Prealgebra 2e is designed to meet scope and sequence requirements for a one-semester prealgebra or basic math course. The book's organization makes it easy to adapt to a variety of course syllabi. The text introduces the fundamental concepts of algebra while addressing the needs of students with diverse backgrounds and learning styles. Each topic builds upon previously developed material to demonstrate the cohesiveness and structure of mathematics. The second edition contains detailed updates and accuracy revisions to address comments and suggestions from users. Dozens of faculty experts worked through the text, exercises and problems, graphics, and and solutions to identify areas needing improvement. Though the authors made significant changes and enhancements, exercise and problem numbers remain nearly the same in order to ensure a smooth transition for faculty. The first edition of Prealgebra by OpenStax is available in web view in the ancillaries.
1 Whole Numbers -- 2 The Language of Algebra -- 3 Integers -- 4 Fractions -- 5 Decimals -- 6 Percents -- 7 The Properties of Real Numbers -- 8 Solving Linear Equations -- 9 Math Models and Geometry -- 10 Polynomials -- 11 Graphs
In English.
Description based on online resource
Keywords: Mathematics -- Textbooks